A computational study of branch-wise curvature in idealized coronary artery bifurcations - Vishesh Kashyap (Elsevier, 2020)
The curvature of coronary arteries can significantly influence their hemodynamics, particularly at coronary bifurcations. The present work aims to investigate the effect of individual branch curvatures on atherosclerotic susceptibility using idealized left coronary bifurcations with dimensions from literature, through computational fluid dynamics (CFD). The bend angle has been used as the metric for curvature, being varied from 0° to 60° for each branch to cover a majority of the population, while keeping the other two branches at 0°. Hemodynamic indicators time-averaged wall shear stress (TAWSS), oscillating shear index (OSI) and relative residence time (RRT) have been studied in the analysis. The results indicate that the individual curvature of each branch of the coronary bifurcation has an impact on the hemodynamics of all three branches. The curvature of either of the branches most significantly impacts the LAD branch, with an increase in the low TAWSS (12% for LM and 20% for LAD branch curvature) and high RRT areas (13% for LAD and 15% for LCx branch curvature) being observed. It may hence be said to be most susceptible to the formation of atherosclerotic lesions. The OSI is observed to be impacted only in the curved branch. In general, an increase in curvature is associated with an increase in the TAWSS. The high RRT area decreases (12%) with LM branch curvature, is negligibly variant for LAD branch curvature and increases (9%) with LCx branch curvature.